Comparative analysis of sedative consumption during ICU stay COVID-19 (Research, Society and Development, 2021)
Introduction: Patients hospitalized in Intensive Care Units (ICU) due to COVID-19 have severe disease development and need sedative administration, just as patients in regular ICUs. Objectives: Fentanyl, Midazolam, and Propofol consumption by patients admitted in COVID-19 ICUs and conventional ICUs, between October 2020 and April 2021, were evaluated and analyzed; subsequently, a comparison between both was established. Methodology: Descriptive exploratory research in a private hospital in the municipality of Cascavel-PR based on electronic medical records and prescriptions. Results: 50 patients were analyzed, of which 25 were from conventional ICUs and 25 from COVID-19 ICUs. In COVID-19 ICUs the average of Midazolam consumption days was almost ten above regular ICUs'. Fentanyl consumption days represented slightly more than twice in COVID-19 ICUs, and milligram (mg) consumption was also higher. As to Propofol, its consumption in COVID-19 ICUs was found to be remarkably superior to conventional ICUs both in days and milligrams; however, the mortality rate was higher in regular ICUs. Conclusion: It has been shown that there is much to learn about the management of these patients; since it is a recent disease, there is not a right and sure approach to be made.